Insulating rod material based on modified epoxy material and preparation method thereof

Through the preparation method of modified epoxy materials, the problems of insulation deterioration and poor material compatibility in humid and hot environments are solved, and the insulation, corrosion resistance and flame retardant properties are improved, ensuring the long-term stability and safety of the material.

CN119752112AActive Publication Date: 2025-04-04STATE GRID ANHUI ULTRA HIGH VOLTAGE CO

Patent Information

Application Number
CN202411810526.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-04
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing insulating rod materials are prone to deterioration in humid and hot environments, and the compatibility of glass fibers and epoxy resins is poor, resulting in unstable material performance, and the oxygen index of epoxy resins is low, which poses safety risks.

Method used

Using modified epoxy materials, insulating rod material with excellent insulation and corrosion resistance is prepared by mixing bisphenol epoxy resin, polybicyclopentadiene, modified glass fiber, curing accelerator, antioxidant and lubricant, and thoroughly mixing in a high-speed mixer.

Benefits of technology

The insulation, corrosion resistance, flame retardant properties, mechanical properties and oxidation resistance of insulating rod materials are significantly improved, and the performance is long-term and stable, reducing safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180438730000031
    Figure BDA0005180438730000031
  • Figure BDA0005180438730000041
    Figure BDA0005180438730000041
  • Figure BDA0005180438730000091
    Figure BDA0005180438730000091
Patent Text Reader

Abstract

The invention discloses an insulating rod material based on a modified epoxy material and a preparation method thereof, and belongs to the technical field of insulating rods. Comprising the following raw materials in parts by weight: 70-90 parts of bisphenol epoxy resin, 15-25 parts of polydicyclopentadiene, 10-20 parts of modified glass fibers, 1-3 parts of a curing accelerator, 4-12 parts of an antioxidant and 2-4 parts of a lubricant. The prepared insulating rod material takes bisphenol epoxy resin as a matrix, so that the insulating rod material is endowed with excellent insulativity and corrosion resistance; wherein the antioxidant can greatly enhance the oxidation resistance of the insulating rod material; wherein the modified glass fiber not only can promote curing of the epoxy resin, but also can remarkably enhance flame retardance, mechanical properties and heat resistance to a certain degree of the insulating rod material, and the performance is long and stable; therefore, the insulating rod material prepared by the invention is good in insulativity and corrosion resistance, has stable and efficient flame retardance, mechanical properties, oxidation resistance and heat resistance to a certain degree, and is halogen-free, flame-retardant and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of insulating rods, and in particular, relates to an insulating rod material based on modified epoxy material and a preparation method thereof. Background Art

[0002] The insulating rod, also known as the switch rod or the link rod, consists of two parts: the working head and the insulating rod body. It is an insulating tool mainly used to operate live equipment for a short time, such as connecting or disconnecting high-voltage disconnectors, drop fuses, installing and removing portable grounding wires, as well as for measurement and testing. The insulating rod is one of the most commonly used safety tools for power workers and is widely used in power work.

[0003] Because of the special working environment of the insulating rod, it is also required to have higher performance. The performance of the insulating rod mainly depends on the rod material of the insulating rod. Therefore, it is of great significance to improve the performance of the insulating rod material. At present, the material of the insulating rod is widely used as a solid composite insulating material, generally adding glass fiber as a reinforcement in the epoxy resin matrix. This method makes the material of the insulating rod have high mechanical strength and good insulation. However, as an inorganic material, glass fiber has poor compatibility with the epoxy resin matrix and is unevenly dispersed in the epoxy resin matrix, making it difficult to fully exert the performance of glass fiber. In addition, the insulating rod is easily corroded by the hot and humid environment under long-term operating conditions, resulting in insulation degradation, resulting in loss of insulation performance, and then affecting power work. Not only that, the oxygen index of epoxy resin is low, and when engaged in electrical work, the safety risk is high, which limits its use. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of insulating rod technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an insulating rod material based on a modified epoxy material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing an insulating rod material based on a modified epoxy material comprises the following steps:

[0007] Bisphenol epoxy resin, polydicyclopentadiene (PDCPD), modified glass fiber, curing accelerator, antioxidant and lubricant are mixed, added into a high-speed mixer, mixed for 45 minutes to make the components fully mixed, poured into a twin-screw extruder for melt blending and extrusion, and cooled to room temperature after discharge to obtain an insulating rod material based on modified epoxy material.

[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 70-90 parts of bisphenol epoxy resin, 15-25 parts of polydicyclopentadiene, 10-20 parts of modified glass fiber, 1-3 parts of curing accelerator, 4-12 parts of antioxidant, and 2-4 parts of lubricant.

[0009] Furthermore, the curing accelerator is one of triethylamine, triethanolamine and o-hydroxybenzyldimethylamine.

[0010] Furthermore, the lubricant is one of zinc stearate, magnesium stearate and epoxidized soybean oil.

[0011] Furthermore, the antioxidant is prepared by compounding antioxidant 1010 and antioxidant 168 in a mass ratio of 3:1.

[0012] The bisphenol epoxy resin is used as the matrix to give the insulating rod material excellent insulation and corrosion resistance; the added polydicyclopentadiene not only has good insulation, but also can improve the heat resistance and mechanical properties of the rod material; the curing accelerator is a tertiary amine accelerator, which can effectively promote the curing of the epoxy resin; the added antioxidant is a compound of a hindered phenol antioxidant and a phosphite auxiliary antioxidant, the two can play a synergistic role and greatly enhance the antioxidant properties of the insulating rod material.

[0013] Furthermore, the modified glass fiber is prepared by the following steps:

[0014] S1. Mix 2-aminobenzimidazole, piperidine (condensing agent) and toluene in a three-necked flask equipped with a stirring device, heat to 50° C., stir until the solid is completely dissolved, add glutaraldehyde, and keep the reaction for 6 hours. After the reaction is completed, cool naturally, filter, and distill under reduced pressure to remove the solvent, wash with anhydrous ethanol 2-3 times, and dry in vacuo to obtain intermediate 1; the ratio of 2-aminobenzimidazole, piperidine, toluene and glutaraldehyde is 13.3 g:15 mL:100 mL:11.8 g;

[0015] Under the action of the condensing agent, the amino group on 2-aminobenzimidazole condenses with the aldehyde group on glutaraldehyde to form an imine group (C=N Schiff base structure), and by controlling the molar ratio of the two to be close to 1:1 and a slight excess of glutaraldehyde, only one aldehyde group on glutaraldehyde participates in the reaction to obtain intermediate 1; the specific reaction process is as follows:

[0016]

[0017] S2. In a three-necked flask equipped with a stirring device, the intermediate 1, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, piperidine and N,N-dimethylformamide (DMF) were mixed and stirred uniformly, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 6 hours. After the reaction was completed, it was naturally cooled, filtered, and part of the solvent was removed by vacuum distillation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:4), the eluent was removed by rotary evaporation, and vacuum dried to obtain intermediate 2; the ratio of the amount of intermediate 1, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, piperidine, and N,N-dimethylformamide was 21.5 g:25.6 g:15 mL:150 mL;

[0018] Under the action of the condensing agent, the amino group on 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane condenses with the aldehyde group on the intermediate 1 to form an imine group (C=N Schiff base structure), and by controlling the molar ratio of the two to be close to 1:1 and a slight excess of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, only one amino group on 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane participates in the reaction to obtain the intermediate 2; the specific reaction process is as follows:

[0019]

[0020] S3, after cleaning and drying the glass fiber in an acetone solution, placing it in a hydrochloric acid solution for 8 hours and then drying it, placing the treated glass fiber in water, adding silane coupling agent KH-560 to react at room temperature for 6 hours, drying it at 80°C for 4 hours, then ultrasonically cleaning it in an ethanol solution for 20 minutes, and finally vacuum drying it at 100°C for 2 hours to obtain a pre-modified glass fiber; the ratio of the amount of glass fiber, hydrochloric acid solution, water, and silane coupling agent KH-560 is 1g:100mL:100mL:4.5g;

[0021] The glass fiber is pre-modified by using silane coupling agent KH-560 so that epoxy groups are connected to its surface to obtain pre-modified glass fiber;

[0022] S4, add N, N-dimethylformamide and pre-modified glass fiber to a flask, disperse evenly by ultrasonication for 15 minutes, add intermediate 2, slowly heat to 95°C, turn on magnetic stirring (speed 1200r / min), stop heating after stirring for 6 hours, let it stand, filter after the temperature in the reaction bottle drops to 30°C, wash with anhydrous ethanol 3-4 times, freeze-dry to obtain modified glass fiber; the ratio of N, N-dimethylformamide, pre-modified glass fiber, and intermediate 2 is 100mL:1g:8.5g;

[0023] The epoxy groups on the surface of the pre-modified glass fiber can undergo a ring-opening reaction with the amino groups on the intermediate 2 molecule to obtain a modified glass fiber;

[0024] Glass fiber is a high-strength filling material. By modifying it, the modified glass fiber is grafted with organic molecular chains through chemical bonding, that is, an organic layer is formed on its surface, which can improve the surface hydrophobicity of the glass fiber, improve the compatibility of the glass fiber and the epoxy resin matrix, make the modified glass fiber dispersed evenly in the matrix, reduce the occurrence of agglomeration, give full play to the performance of the glass fiber, and greatly enhance the mechanical properties of the matrix; not only that, the modified glass fiber also contains -Si-O-Si- segment, benzimidazole and Schiff base structure, among which -Si-O-Si- segment is a good flame retardant and smoke suppression component, which can not only improve the flame retardancy of the matrix It can also have a certain smoke suppression effect; in addition, since the Si-O bond has a high bond energy, it can improve the heat resistance of the matrix to a certain extent; the C=N double bond in the introduced Schiff base structure can generate a carbon-nitrogen six-membered ring at high temperature. This type of six-membered ring structure enables the matrix to form a stable cross-linked network, which synergizes with the -Si-O-Si- segment and greatly enhances the flame retardant properties of the matrix; finally, the pyridine nitrogen in the benzimidazole structure can react with the epoxy group with high reaction activity in the epoxy resin, and can synergize with the tertiary amine accelerator to promote the curing of the epoxy resin, so that the epoxy resin matrix forms a cross-linked three-dimensional network macromolecular polymer, and improves the various properties of the epoxy resin matrix;

[0025] It should be added that the modified glass fiber grafted with organic molecular chains can effectively prevent the migration and seepage of small organic molecules and ensure the durability of various performance properties.

[0026] Beneficial effects of the present invention:

[0027] 1. The insulating rod material prepared by the present invention uses bisphenol epoxy resin as a matrix to give the insulating rod material excellent insulation and corrosion resistance;

[0028] 2. The added antioxidant is a compound of hindered phenol antioxidant and phosphite auxiliary antioxidant, which can play a synergistic role and greatly enhance the antioxidant performance of the insulating rod material;

[0029] 3. Compared with ordinary glass fibers, the modified glass fibers have better compatibility with epoxy resin matrix, which can not only promote the curing of epoxy resin, but also significantly enhance the flame retardancy, mechanical properties and heat resistance of insulating rod materials to a certain extent, and the performance is long-term and stable;

[0030] Therefore, the insulating rod material prepared by the present invention has good insulation and corrosion resistance, stable and efficient flame retardancy, mechanical properties, anti-oxidation and a certain degree of heat resistance, and is halogen-free and flame retardant, environmentally friendly, and has important application value in the field of insulating rod technology. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Embodiment 1

[0033] Preparation of modified glass fiber:

[0034] S1. In a three-necked flask equipped with a stirring device, 13.3 g of 2-aminobenzimidazole, 15 mL of piperidine and 100 mL of toluene were mixed, the temperature was raised to 50° C., and the mixture was stirred until the solid was completely dissolved. 11.8 g of glutaraldehyde was added, and the mixture was kept warm for 6 h. After the reaction was completed, the mixture was naturally cooled, filtered, and the solvent was removed by distillation under reduced pressure. The mixture was washed with anhydrous ethanol for 2-3 times, and dried in vacuo to obtain intermediate 1.

[0035] S2, in a three-necked flask equipped with a stirring device, 21.5g of intermediate 1, 25.6g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 15mL of piperidine and 150mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 6h. After the reaction was completed, it was naturally cooled, filtered, and part of the solvent was distilled off under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:4), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 2;

[0036] S3, 1g of glass fiber was washed and dried in an acetone solution, and then placed in 100mL of hydrochloric acid solution (mass fraction 12%) for 8h and dried, the treated glass fiber was placed in 100mL of water, 4.5g of silane coupling agent KH-560 was added to react at room temperature for 6h, and then dried at 80°C for 4h, and then ultrasonically washed in an ethanol solution for 20min, and finally vacuum dried at 100°C for 2h to obtain pre-modified glass fiber;

[0037] S4. Add 100 mL of N,N-dimethylformamide and 1 g of pre-modified glass fiber into a flask, disperse evenly by ultrasonication for 15 min, add 8.5 g of intermediate 2, slowly heat up to 95 °C, start magnetic stirring (speed 1200 r / min), stop heating after stirring for 6 h, let it stand, and after the temperature in the reaction bottle drops to 30 °C, filter it, wash it 4 times with anhydrous ethanol, and freeze-dry it to obtain modified glass fiber.

[0038] Embodiment 2

[0039] Preparation of modified glass fiber:

[0040] S1. In a three-necked flask equipped with a stirring device, 26.6 g of 2-aminobenzimidazole, 30 mL of piperidine and 200 mL of toluene were mixed, the temperature was raised to 50° C., and the mixture was stirred until the solid was completely dissolved. 23.6 g of glutaraldehyde was added, and the mixture was kept warm for 6 h. After the reaction was completed, the mixture was naturally cooled, filtered, and the solvent was removed by distillation under reduced pressure. The mixture was washed twice with anhydrous ethanol and dried under vacuum to obtain intermediate 1.

[0041] S2, in a three-necked flask equipped with a stirring device, 43.0g of intermediate 1, 51.2g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 30mL of piperidine and 300mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 6h. After the reaction was completed, it was naturally cooled, filtered, and part of the solvent was distilled off under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:4), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 2;

[0042] S3, 2g of glass fiber was washed and dried in an acetone solution, and then placed in a 200mL hydrochloric acid solution (mass fraction 12%) for 8h and dried, the treated glass fiber was placed in 200mL water, 9g of silane coupling agent KH-560 was added, and the reaction was carried out at room temperature for 6h, and then dried at 80°C for 4h, and then ultrasonically washed in an ethanol solution for 20min, and finally vacuum dried at 100°C for 2h to obtain a pre-modified glass fiber;

[0043] S4. Add 200 mL of N,N-dimethylformamide and 2 g of pre-modified glass fiber into a flask, disperse evenly by ultrasonication for 15 min, add 17 g of intermediate 2, slowly heat up to 95 °C, start magnetic stirring (speed 1200 r / min), stop heating after stirring for 6 h, let it stand, and after the temperature in the reaction bottle drops to 30 °C, filter it, wash it 4 times with anhydrous ethanol, and freeze-dry it to obtain modified glass fiber.

[0044] Embodiment 3

[0045] 70g of bisphenol epoxy resin, 15g of polydicyclopentadiene, 10g of the modified glass fiber prepared in Example 1, 1g of triethylamine, 4g of antioxidant (prepared by compounding 3g of antioxidant 1010 and 1g of antioxidant 168) and 2g of zinc stearate were mixed, added to a high-speed mixer, and mixed for 45 minutes to fully mix the components. The mixture was then poured into a twin-screw extruder for melt blending and extrusion. The material was cooled to room temperature after discharge to obtain an insulating rod material based on a modified epoxy material.

[0046] Embodiment 4

[0047] 80g of bisphenol epoxy resin, 20g of polydicyclopentadiene, 15g of the modified glass fiber prepared in Example 2, 2g of triethanolamine, 8g of antioxidant (prepared by compounding 6g of antioxidant 1010 and 2g of antioxidant 168) and 3g of magnesium stearate were mixed, added to a high-speed mixer, and mixed for 45 minutes to fully mix the components. The mixture was then poured into a twin-screw extruder for melt blending and extrusion. The material was cooled to room temperature after discharge to obtain an insulating rod material based on a modified epoxy material.

[0048] Embodiment 5

[0049] 90 g of bisphenol epoxy resin, 25 g of polydicyclopentadiene, 20 g of the modified glass fiber prepared in Example 1, 3 g of triethanolamine, 12 g of an antioxidant (prepared by compounding 9 g of antioxidant 1010 and 3 g of antioxidant 168) and 4 g of magnesium stearate were mixed, added to a high-speed mixer, and mixed for 45 minutes to fully mix the components. The mixture was then poured into a twin-screw extruder for melt blending and extrusion. The material was cooled to room temperature after discharge to obtain an insulating rod material based on a modified epoxy material.

[0050] Comparative Example 1

[0051] Ordinary glass fibers of the same mass are used to replace the modified glass fibers in Example 5, and the remaining steps are the same as those in Example 5 to obtain an insulating rod material.

[0052] Comparative Example 2

[0053] A commercially available flame retardant epoxy resin material was used.

[0054] The following performance tests were performed on Examples 3 to 5 and Comparative Examples 1 and 2 according to different test standards:

[0055] Adopt the national standard GB 13398-2003 "Hollow insulating tubes, foam-filled insulating tubes and solid insulating rods for live working" for tensile strength and normal resistivity;

[0056] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to measure the limiting oxygen index of the sample before and after standing at room temperature for 180 days;

[0057] Thermal aging test: Place the sample in an environment of 150°C, and after standing for 24 hours, test the tensile strength of the sample (GB13398-2003), and calculate the tensile strength retention rate; tensile strength retention rate = tensile strength after test / tensile strength before test × 100%;

[0058] The measurement results are shown in the following table:

[0059]

[0060] It can be seen from the above table that the flame retardancy, mechanical properties and heat resistance of the insulating rod material prepared in the embodiments of the present invention are higher than those in the comparative example, and the performance is long-lasting and stable; in addition, as the content of modified glass fiber in embodiments three to five is continuously increased, various properties of the insulating rod material are enhanced. Therefore, the present invention has important application value in the field of insulating rod technology.

[0061] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0062] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an insulating rod material based on a modified epoxy material, characterized in that: The following steps are involved: Bisphenol epoxy resin, polydicyclopentadiene, modified glass fiber, curing accelerator, antioxidant and lubricant are mixed, added into a high-speed mixer for mixing, poured into a twin-screw extruder for melt blending and extrusion, and cooled to room temperature after discharge to obtain an insulating rod material based on modified epoxy resin.

2. The method for preparing an insulating rod material based on a modified epoxy material according to claim 1, characterized in that: The modified glass fiber is prepared by the following steps: S1, 2-aminobenzimidazole, piperidine and toluene were mixed, the temperature was raised to 50°C, glutaraldehyde was added, the temperature was kept for 6 hours, the reaction was completed, the mixture was naturally cooled, filtered, vacuum distilled, washed, and vacuum dried to obtain intermediate 1; S2, mixing intermediate 1, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, piperidine and N,N-dimethylformamide, stirring evenly, reacting at 60° C. for 6 h, and after the reaction is completed, naturally cooling, filtering, vacuum distillation, column chromatography purification, rotary evaporation, and vacuum drying to obtain intermediate 2; S3, washing and drying the glass fiber in an acetone solution, placing it in a hydrochloric acid solution for 8 hours and then drying it, placing the treated glass fiber in water, adding silane coupling agent KH-560 to react at room temperature for 6 hours, drying it at 80°C for 4 hours, then ultrasonically washing it in an ethanol solution for 20 minutes, and vacuum drying it to obtain a pre-modified glass fiber; S4. Add N,N-dimethylformamide and pre-modified glass fiber into a flask, disperse them evenly by ultrasonication for 15 minutes, add intermediate 2, slowly heat up to 95°C, start magnetic stirring, stop heating after stirring for 6 hours, let it stand, filter, wash and dry to obtain modified glass fiber.

3. The method for preparing an insulating rod material based on a modified epoxy material according to claim 2, characterized in that: In step S1, the ratio of 2-aminobenzimidazole, piperidine, toluene and glutaraldehyde is 13.3 g:15 mL:100 mL:11.8 g.

4. The method for preparing an insulating rod material based on a modified epoxy material according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, piperidine, and N,N-dimethylformamide is 21.5 g:25.6 g:15 mL:150 mL.

5. The method for preparing an insulating rod material based on a modified epoxy material according to claim 2, characterized in that: In step S3, the ratio of the amount of glass fiber, hydrochloric acid solution, water, and silane coupling agent KH-560 is 1 g: 100 mL: 100 mL: 4.5 g.

6. The method for preparing an insulating rod material based on a modified epoxy material according to claim 2, characterized in that: In step S4, the ratio of the amount of N,N-dimethylformamide, pre-modified glass fiber, and intermediate 2 is 100 mL: 1 g: 8.5 g.

7. The method for preparing an insulating rod material based on a modified epoxy material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 70-90 parts of bisphenol epoxy resin, 15-25 parts of polydicyclopentadiene, 10-20 parts of modified glass fiber, 1-3 parts of curing accelerator, 4-12 parts of antioxidant, and 2-4 parts of lubricant.

8. The method for preparing an insulating rod material based on a modified epoxy material according to claim 1, characterized in that: The antioxidant is prepared by compounding antioxidant 1010 and antioxidant 168 in a mass ratio of 3:

1.

9. An insulating rod material based on modified epoxy material, characterized in that: Prepared according to the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Insulating rod body material and preparation method thereof

    CN106633638A

  • Epoxy resin composite insulating material and preparation method thereof

    CN109294166A

  • Epoxy glass fiber insulating rod material and preparation method thereof

    CN115948027A

  • Preparation method of high-impact-resistance and high-insulating-strength composite bushing material with core-shell structure

    CN117467240A

  • Method for preparing glass-fiber insulating rod coatedwith epoxy and glass-fiber insulating rod using themethod

    KR100737279B1

Cited By

  • Anti-aging resin core rod for composite insulator and preparation method of anti-aging resin core rod

    CN121203346A

  • An aging-resistant resin core rod for composite insulators and its preparation method

    CN121203346B